9 - Colonialism, Customary Law and the Post-Colonial State in Africa: The Case of Nigeria: DOI: 10.4314/ad.v30i4.22246 - Yakubu, John Ademola (Africa Development, 2022)
Colonialism became a fact of life in many African countries. An effect of colo nialism especially in the former British colonized countries was the transplanta tion of the British legal system, which led to recognition of both systems and the gradual relegation of the indigenous system otherwise called customary law. The use and effect of these customary laws became dependent on the permis sive extent of the general law. In its regulated state, its operation became de pendent on the satisfaction of the rules of common law equity and good con science. Other rules as to the amenability of customary law and proof became established. Notwithstanding the relegation of the rules of customary law vis-à vis the general law, these rules have survived to date. Islamic law which was usually regarded as a variant of customary law is beginning to have its separate status. This article shall examine the impact of colonialism on customary law especially in the post colonial Nigerian state.